Iridium-catalyzed allylic vinylation and asymmetric allylic amination reactions with o-aminostyrenes - Ye, Ke-Yin; He, Hu; Liu, Wen-Bo; Dai, Li-Xin; Helmchen, Günter; You, Shu-Li (Journal of the American Chemical Society, 2011)
An Ir-catalyzed allylic vinylation reaction of allyl carbonates with o-aminostyrene derivatives has been realized, providing skipped (Z,E)-diene derivatives. With (E)-but-2-ene-1,4-diyl dimethyl dicarbonate as the substrate, an efficient enantioselective synthesis of 1-benzazepine derivatives via an Ir-catalyzed domino allylic vinylation/intramolecular allylic amination reaction has been developed. Mechanistic studies of the allylic vinylation reaction have been carried out, and the results suggest that the leaving group of the allylic precursor plays a key role in directing the reaction pathway. Screening of various allylic precursors showed that Ir-catalyzed reactions of allyl diethyl phosphates with o-aminostyrene derivatives proceed via an allylic amination pathway. A subsequent ring-closing metathesis (RCM) reaction of the amination products led to a series of enantiomerically enriched 1,2-dihydroquinoline derivatives. Their utility is indicated by an asymmetric total synthesis of (−)-angustureine.
Gesehen am 12.12.2022